Anti-programmed cell death protein 1 (anti-PD1) immunotherapy induced autoimmune polyendocrine syndrome type II (APS-2): a case report and review of the literature. Issue 1 (5th September 2019) - Gunjur, Ashray; Klein, Oliver; Kee, Damien; Cebon, Jonathan
Abstract : Background: Autoimmune polyendocrine syndrome type II (APS-2) is a rare constellation of autoimmune hypoadrenalism, thyroid dysfunction and/or type 1 diabetes (T1DM), usually occurring in the 3rd or 4th decades and associated with a human leukocyte antigen (HLA) DR3 or DR4 serotype. We detail the first report of an elderly woman developing the full triad of APS-2 shortly after commencing anti-programmed cell death protein 1 (anti-PD1) immune checkpoint inhibition for unresectable melanoma and review the literature for similar presentations secondary to anti-PD1 axis therapy. Case: A 78-year-old female with advanced unresectable BRAF wild-type melanoma was treated with pembrolizumab (2 mg/kg 3-weekly). Three weeks following the first dose she developed fulminant autoimmune diabetes, with an initially low C-peptide denoting rapid destruction of ß-islet cells. Following stabilisation of her diabetes, two further doses of pembrolizumab was administered. She then represented with symptomatic hypoadrenalism and hypothyroidism, consistent with APS-2. Her HLA class II genotype was HLA-DRB1*04.16 (DR4 serotype), a recognised association with this syndrome. Her melanoma responded rapidly to anti-PD1 therapy, and a complete response (CR) was attained after four doses of pembrolizumab. Treatment was discontinued and her CR is ongoing. Conclusion: This is the first report of the full triad of APS-2 developing in a genetically susceptible individual at the age of 78 after treatment with an anti-PD1 agent. Although scarcely reported, a literature review of similar reports seems to indicate a predilection for this syndrome in patients with HLA-DR4 serotypes. HLA Class II typing is not routinely recommended, but may provide useful predictive information for patients at risk of poly-endocrinopathy even in patients without a relevant personal or family history. Additional studies are required to determine if such testing would be useful and/or cost effective.